Entre o mercado e a construção social: uma análise da experiência da implantação doPRONAF-infraestrutura e PRONAT nos territórios do Mato Grande-RN e sertão do Apodi-RN (1997 - 2010) - Reis, Fábio Henrique Vale dos (2012)
Analyzes the development experience in the Territories of Mato Grande and Sertão do Apodi in the state of Rio Grande do Norte, evaluating the actions of the National Program for Strengthening Family Agriculture, specifically the line of infrastructure (PRONAF-INFRA), and the National Program for Sustainable Development of Rural Territories (PRONAT) in these territories. Summarizes the various rural development approaches and takes the theoretical assumptions of territorial development, the concept of constructed territory and market-plan territory, further the cycle model to analyze public policies selected these experiences. Thus, we propose to test the hypothesis that most of the actions implemented would lead to the formation of market-plan territories, in other words, perceived only as a platform for the presentation of projects. The literature and documents, combined with case studies, interviews and direct observation of the meetings of committees, showed that, despite two boards are under the same laws, rules and formal regulations, have clear differences when considering the theory and concepts that were used as reference. The Apodi s territory is closer to a constructed space thus the search for a broader agenda, more autonomous and more appropriate to the reality experienced by local actors. On other hand the Territory of Mato Grande had the characteristics of a market-plan territory more present. As the result, the territory of Sertão do Apodi accesses not only as part of a greater number of policies and funding sources, ensuring a greater and more diverse investment volume than the territory of Mato Grande. Despite these differences, studies have shown that territorial boards surveyed are still far from becoming the main forum for managing the development from conception planning socially constructed. Showed, finally, that territorial development strategy is relevant, but requires a long walk and a deep and continuous learning process to be successfully implemented in rural areas of Northeast Brazil